Perioperative and adjuvant chemotherapy on survival in advanced gastric cancer following gastrectomy with D2 lymphadenectomy - Luna-Córdova, Cesia J. (2025)
Objective: To describe the effectiveness of perioperative chemotherapy and adjuvant chemotherapy in the survival of patients with gastric carcinoma after gastrectomy with D2 lymphadenectomy (T2-T4a) and to determine the association between the intervening factors of the study and the survival of this group. Materials and methods: Observational study, retrospective cohorts, in patients who received perioperative or adjuvant chemotherapy at a Peruvian cancer institute from January 2007 to December 2022. To determine actuarial survival, the Kaplan-Meier method and the log-rank test were used to compare 2 survival curves. Results: A total population of 82 patients was evaluated, of which 46 received adjuvant chemotherapy and 36 perioperative chemotherapy, with the most commonly used regimen being CAPOX and EOX/EOX, respectively. Clinical characteristics did not significantly influence overall survival and only the primary tumor (T) had a statistically significant association, with T4a being more frequent in the perioperative chemotherapy group than in the adjuvant modality group (80.6% vs 47.8%; p=0.002). When comparing both therapeutic modalities, it was evident that patients who received perioperative chemotherapy had a longer survival at 5 years (53.2%), however, this was not statistically significant (p=0.230). Conclusions: Perioperative chemotherapy presented greater survival compared to adjuvant chemotherapy at 12, 36 and 60 months; however, these differences were not statistically significant.